Sustaining Urban Spatial Network of Historical Communities Through the Reuse of Temple Grounds and Social Space – A Case Study of Rattanakosin, Bangkok - Paksukcharern, Khaisri (Nakhara : Journal of Environmental Design and Planning, 2016)
Old communities in Rattanakosin, a historical center of Bangkok, have been the model of a vibrant mixuse urban area where residences, temples, schools and local retailers are clustered in close proximity. The Rattanakosin area has distinctive spatial characteristics hardly found in other areas of Bangkok; small urban blocks, a dense grid network for pedestrian only, and a large number of Buddhist temples well integrated within communities. The mapping of space usage reveals how local inhabitants, as well as tourists, interact within a series of public open spaces. How this interaction differs at various times and activities are in fact spatially related. This paper aims to clarify how historical communities in Bangkok can sustain their viability through socio-spatial dialectic patterns by using the analysis of a spatial configuration network in relation to space use patterns. It also reveals that Buddhist temple grounds, once important public spaces transitioning between sacred temple areas and profane urban surroundings, no longer act as important social spaces in local communities. The analytical results suggest that sustaining the urban vitality of historical communities in the Rattanakosin could be done by reintegrating the existing small public open spaces in the area. This approach addresses the temple grounds within the internal pedestrian grid network as well as the external road network. The interconnecting and well hierarchical urban spatial network will create a good mix of local inhabitants and tourists in the area.